PB

Thu gọn biểu thức M = 4x 2 − 3x + 5 x 3 − 1 − 1 − 2x x 2 + x + 1 − 6 x − 1  ta được?

A.  − 12x x 3 − 1

B.  − 12 x 3 − 1

C.  − x x 3 − 1

D.  3 x 3 − 1

CT
31 tháng 12 2019 lúc 3:12

Điều kiện:  x ≠ 1

M   =   4 x 2 − 3 x + 5 x 3 − 1 − 1 − 2 x x 2 + x + 1 − 6 x − 1 = 4 x 2 − 3 x + 5 x − 1 x 2 + x + 1 − 1 − 2 x x 2 + x + 1 − 6 x − 1 = 4 x 2 − 3 x + 5 x − 1 x 2 + x + 1 − 1 − 2 x x − 1 x 2 + x + 1 − 6 x 2 + x + 1 x − 1 = 4 x 2 − 3 x + 5 x − 1 x 2 + x + 1 − x − 1 − 2 x 2 + 2 x x 2 + x + 1 − 6 x 2 + 6 x + 6 x − 1 = 4 x 2 − 3 x + 5 + 2 x 2 − 3 x + 1 − 6 x 2 − 6 x − 6 x − 1 x 2 + x + 1 = − 12 x x 3 − 1

Đáp án cần chọn là A

Bình luận (0)